CONSUMER EXPERIENCE AND THE ROLE OF SERVICE QUALITY IN AUTOMOBILE RETAILS - Damian, Ieda Pelogia Martins; Merlo, Edgard Monforte (Contextus - Contemporary Journal of Economics and Management, 2014)
To understand the influence of the consumption experience, their relationships with service quality and its implications for managers can be considered important contributions. The importance of the automotive sector and the relationships between the above concepts led to the goal of this study that was to examine the role of the consumer experience and the quality of automotive service. It was applied a questionnaire sent to 10,000 emails across the country and 444 valid responses were obtained. The results showed that the aspects related to service quality were considered as important as the elements related to the consumption experience. Aspects of the leading consumer experience by consumers relate to the pleasure of buying, assortment and prices. Regarding quality of services, the highlighted elements were related to high quality services, care of employees, attendance time and meeting deadlines.